Influence of the acquaintance of risk factors of breast cancer amongst women in the age of 50-69 years as for performing prophylactic examinations by them - Szadowska-Szlachetka, Zdzisława Cecylia; Łuczyk, Marta; Pitraszek, Agata; Łuczyk, Robert Jan; Stanisławek, Andrzej; Charzyńska-Gula, Marianna (Journal of Education, Health and Sport, 2016)
Szadowska-Szlachetka Zdzisława, Łuczyk Marta, Pietraszek Agata, Łuczyk Robert, Stanisławek Andrzej, Charzyńska‑Gula Marianna. Influence of the acquaintance of risk factors of breast cancer amongst women in the age of 50-69 years as for performing prophylactic examinations by them. Journal of Education, Health and Sport. 2016;6(3):21-34. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.47237 http://ojs.ukw.edu.pl/index.php/johs/article/view/3416 https://pbn.nauka.gov.pl/works/718846 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.01.2016. Revised 12.02.2016. Accepted: 27.02.2016. Influence of the acquaintance of risk factors of breast cancer amongst women in the age of 50-69 years as for performing prophylactic examinations by them Zdzisława Szadowska-Szlachetka1, Marta Łuczyk1, Agata Pietraszek1, Robert Łuczyk2, Andrzej Stanisławek1, Marianna Charzyńska-Gula3 1 Chair of Oncology and Environmental Care of Medical University of Lublin 2 Chair of Internal Medicine with Department of Internal Nursing of Medical University of Lublin 3 State Higher Vocational School Memorial of Prof. Stanislaw Tarnowski in Tarnobrzeg Keywords: breast cancer, risk factors, prophylactic studies, mammography. Abstract Breast cancer is the most frequent as well as, at the same time, most dangerous of cancers affecting women with regard to diagnosing it in the advanced stage being also characterised with the top degree of mortality of female patients worldwide. At present, it is the most frequent malignant tumour affecting Polish women [9]. Awareness of women about risk factors and the early diagnostic testing consisting in self-examination of breasts and also regular performance of mammographic examinations in the appropriate age may reduce, in the significant way, mortality amongst women affected with this illness by its early detecting and curing. This study is aimed at presenting the state of knowledge of women in the age of 50 - 69 concerned with risk factors of breast cancer and the frequency of performing prophylactic examinations by them.